2019
DOI: 10.3390/en12152870
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Operation of Tidal Range Schemes

Abstract: Marine renewable energy, including tidal renewable energy, is one of the less exploited sources of energy that could contribute to energy demand, while reducing greenhouse gas emissions. Amongst several proposals to build tidal range structure (TRS), a tidal lagoon has been proposed for construction in Swansea Bay, in the South West of the UK, but this scheme was recently rejected by the UK government due to the high electricity costs. This decision makes the optimisation of such schemes more important for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 27 publications
(64 reference statements)
8
35
0
Order By: Relevance
“…Neglecting any tidal variations that could develop over the rest of the year, this neap-spring tidal cycle was presumed to be sufficient for this assessment. The estimated annual (neap-spring averaged) energy was then calculated by extrapolating the simulation results over the period of one year [15]. The total electricity generated for the baseline scenario was estimated to be about 578 GWh/year, which was consistent with predictions for past studies [2,13,49].…”
Section: Power Outputsupporting
confidence: 59%
See 3 more Smart Citations
“…Neglecting any tidal variations that could develop over the rest of the year, this neap-spring tidal cycle was presumed to be sufficient for this assessment. The estimated annual (neap-spring averaged) energy was then calculated by extrapolating the simulation results over the period of one year [15]. The total electricity generated for the baseline scenario was estimated to be about 578 GWh/year, which was consistent with predictions for past studies [2,13,49].…”
Section: Power Outputsupporting
confidence: 59%
“…The transfer of mass is included in the continuity Equation (1) through local sink and source terms. The operation of the lagoon can be optimised to generate the maximum energy [15]. Since this is outside the scope of this study, only a typical two-way generation scheme (as suggested by Tidal Lagoon Plc [29]) was considered herein.…”
Section: Tidal Lagoon Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The short-term storage capabilities possessed by tidal power plants is facilitated by the degree of control in scheduling different modes of operation. Combined with the predictable and reliable nature of the tidal resource, this flexible control can unlock economic opportunities [7,8].…”
Section: Introductionmentioning
confidence: 99%